Ghrelin deletion protects against age‐associated hepatic steatosis by downregulating the C/EBPα‐p300/DGAT1 pathway. Issue 1 (12th October 2017) - Guillory, Bobby; Jawanmardi, Nicole; Iakova, Polina; Anderson, Barbara; Zang, Pu; Timchenko, Nikolai A.; Garcia, Jose M.
Summary: Nonalcoholic fatty liver disease (NAFLD) is the most common liver disease worldwide. NAFLD usually begins as low‐grade hepatic steatosis which further progresses in an age‐dependent manner to nonalcoholic steatohepatitis (NASH), fibrosis, cirrhosis, and hepatocellular carcinoma in some patients. Ghrelin is a hormone known to promote adiposity in rodents and humans, but its potential role in hepatic steatosis is unknown. We hypothesized that genetic ghrelin deletion will protect against the development of age‐related hepatic steatosis. To examine this hypothesis, we utilized ghrelin knockout (KO) mice. Although no different in young animals (3 months old), we found that at 20 months of age, ghrelin KO mice have significantly reduced hepatic steatosis compared to aged‐matched wild‐type (WT) mice. Examination of molecular pathways by which deletion of ghrelin reduces steatosis showed that the increase in expression of diacylglycerol O‐acyltransferase‐1 (DGAT1), one of the key enzymes of triglyceride (TG) synthesis, seen with age in WT mice, is not present in KO mice. This was due to the lack of activation of CCAAT/enhancer binding protein‐alpha (C/EBPα) protein and subsequent reduction of C/EBPα‐p300 complexes. These complexes were abundant in livers of old WT mice and were bound to and activated the DGAT1 promoter. However, the C/EBPα‐p300 complexes were not detected on the DGAT1 promoter in livers of old KO mice resulting in lower levels of the enzyme. In conclusion, these studies demonstrate the mechanism by which ghrelin deletion prevents age‐associated hepatic steatosis and suggest that targeting this pathway may offer therapeutic benefit for NAFLD.